The Road To Omaha - Ludlum, Robert, 1927-2001 (London HapperCollins Publishers, 1992)
The outrageous characters from The Road to Gandolfo continue their madcap adventures in a romp around Nebraska that is spurred by the discovery of a secret 1878 treaty with an obscure Indian tribe.
Keywords: Indians of North America--Legal status, laws, etc -- Nebraska--Omaha -- English